2003
DOI: 10.1046/j.1365-2265.2003.01679.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome and mortality after transsphenoidal adenomectomy for acromegaly

Abstract: Our observations confirm that uncontrolled acromegaly increases mortality compared to the general population and that mortality rates similar to the general population are restored once remission is induced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
175
5
20

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(215 citation statements)
references
References 18 publications
15
175
5
20
Order By: Relevance
“…Median age at death in the Belgian survey (68 years in men and 74 years in women) is higher than reported in previous series: 60 years in REA (12), 61 years in Quebec (8) and New Zealand (6), but close to the 64 years for men and 69 years for women in Finland (5) and the 66 years in the West Midlands database (4). By comparison, current life expectancy in Belgium is 75.6 in men and 81.7 years in women.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Median age at death in the Belgian survey (68 years in men and 74 years in women) is higher than reported in previous series: 60 years in REA (12), 61 years in Quebec (8) and New Zealand (6), but close to the 64 years for men and 69 years for women in Finland (5) and the 66 years in the West Midlands database (4). By comparison, current life expectancy in Belgium is 75.6 in men and 81.7 years in women.…”
Section: Discussioncontrasting
confidence: 48%
“…This difference is probably due to selection bias as ultrasound is not systematically performed in every day clinical care, especially if patients are not treated with SSA. On the other hand, the reported prevalence of overt diabetes mellitus (25%), previously reported to be 9-23% (19), is lower than in REA (38%) and in a Canadian study (40%) (8). Underreporting is unlikely, as the non-diabetic patients had normal glucose and HbA1c values at the time of the survey.…”
Section: Discussioncontrasting
confidence: 40%
“…Bates et al (38) were the first to demonstrate that an increased mortality was reduced to normal when GH levels reached !2.5 mg/l. Their observations were supported by numerous further studies (22,26,27,28,29,30,32,38,39) with a pooled SMR of 1.1 (0.9-1.4; PZ0.50) (7). Some research groups reported even lower GH targets: 2 mg/l by Ayuk et al and a further improvement in mortality when GH was reduced to !1 mg/l (23,26).…”
Section: Clinical Studysupporting
confidence: 56%
“…15,22 For most patients, transsphenoidal adenomectomy (TSA) by a dedicated and experienced pituitary neurosurgeon is the first-line treatment option. [23][24][25][26] In addition to surgical treatment, the American Association of Clinical Endocrinologists (AACE) reviews the pharmacological options for the treatment of acromegaly and recommends medical therapy for the treatment of persistent acromegaly and for treatment of patients who are not candidates for surgery. 3,21 The options for medical therapy include: somatostatin analogs, dopaminereceptor agonists, and GH-receptor analogs.…”
Section: Acromegalymentioning
confidence: 99%